Relasi Kiai Pesantren Dengan Kiai Langgar dalam Melestarikan Tradisi Pesantren di Dusun Sasar Kopedi Bluto - Faridatul Jannah (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2023)
It is classified into five different typologies to define Kiai by their function: Pesantren Kiai, Tarekat Kiai, Political Kiai, Stage Kiai and Kiai Langgar. The existence of this classification creates a specification of Kiai's role in society, such as Kiai Pesantren and Kiai langgar. In addition to educate santri in pesantren, Pesantren Kiai also imparts knowledge to the wider community within a hamlet. However, in transforming religious knowledge to the community they need mediation or support of Kiai Langgar. This research will explore the scope of research as follows: First, what is the relationship pattern between Pesantren Kiai and Kiai Langgar as the Care Taker of Pesantren Tradition? Second, what are the forms of Pesantren Traditions preserved in the Relationship between Pesantren Kiai and Kiai Langgar in Sasar Kapedi Bluto Hamlet? Thus, from these two questions, the main focus of this research is the relationship between Pesantren Kiai and Kiai langgar in preserving the pesantren tradition in Sasar Kapedi Bluto hamlet. The theory used in this research is Patron Client Theory developed by James Scoth. The approach used is a qualitative approach with direct field immersion tailored in accordance to the research needs. The data collection methods used are interviews, observation and documentation. The results of the study state, that the relationship pattern formed between Pesantren Kiai and Kiai Langgar in preserving pesantren traditions in Sasar Kapedi Bluto hamlet, develops in three patterns; teacher-student relationship, sharing da'wah tasks and spiritual bond. The forms of pesantren traditions preserved in the relationship between Pesantren Kiai and Kiai Langgar in Sasar Kapedi Bluto Hamlet include: the tradition of Kiai obedience, the tradition of learning the classical book and the tradition of friendship.